Meta-Analysis on Long-Term Outcomes of Pediatric Renal Cancer Survivors Following COG and SIOP Protocols - Raffaele, Alessandro; Gazzaneo, Marta; Busel, Adi; Vatta, Fabrizio; Belgiovine, Cristina; Parigi, Gian Battista; Riccipetitoni, Giovanna (European Journal of Pediatric Surgery, 2022)
Background Pediatric renal cancer survivors have higher rate of chronic renal disease and hypertension. These patients have similar survival rates when treated according to either Children's Oncology Group (COG) or International Society of Pediatric Oncology (SIOP) protocols. We aimed to compare the late outcome of these two approaches.Methods We performed a meta-analysis of all studies from 2000 to 2021; database search using keywords: long-term outcomes OR late effects, nephrectomy, pediatric renal cancer. For each protocol, data were collected, and the “pooled” outcomes were compared. Continuous and dichotomous variables were obtained with a 95% odds ratio.Results Sixteen studies with a total of 715 pediatric renal cancer survivors were analyzed. The mean follow-up time was 17.4 (standard deviation 5.6) years. Reduced renal function and hypertension were the most encountered long-term complications. The mean estimated glomerular filtration rate was similar in both protocols (101.62 vs. 101.70 mL/min/1.73 m2), while the prevalence of hypertension was 23% in COG and 10% in SIOP. The prevalence of secondary malignancy was 1.1% in COG and 6.7% in SIOP (1.1% vs. 6.7%, p ≤ 0.001). Chronic kidney disease was similar in both groups.Conclusion A high prevalence of hypertension was observed among pediatric renal cancer survivors, as well as an increased risk of a secondary tumor. These results emphasize the importance of long-term follow-up into adulthood, to promptly diagnose any long-term side effects of the treatment. Thanks to the increased overall survival, future protocols will pay attention to the reduction of long-term sequelae.
Keywords: pediatric renal cancer; long-term follow-up; side effect of cancer surgery